Morfofonemik Reduplikasi Bahasa Dawan - Benu, Naniana Nimrod; Suparwa, I Nyoman; Putu Putra, Anak Agung (Humanis, 2024)
This article discusses the morphophonemic aspects of reduplication in the Dawan language. The focus on morphophonemic studies is based on the fact that reduplication is a word formation process involving repetition, making exploring the intersection and phonological roles in this process interesting. Data were obtained through observation and interviews. Based on the collected data, it is evident that reduplication can occur with verbs, nouns, adjectives, and adverbs. For example, the noun neno, meaning 'day' has two forms of reduplication neno-neno, which functions as a noun, and "nen-neno," which serves as an adverb. The data also indicate that reduplication in the Dawan language consists of full and partial reduplication. Among these, partial reduplication is the most productive, while full reduplication is often used to emphasize objects or topics, suggesting a pragmatic aspect in full repetition. Common phonological processes found include sound elision and metathesis.